Linking disaster risk reduction, climate change and development - Schipper, E; Thomalla, F; Vulturius, G; Davis, M; Johnson, K (Emerald Group Publishing Limited, 2016)
Purpose The purpose of this paper is to advance the dialogue between the disaster risk reduction (DRR) and adaptation community by investigating their differences, similarities and potential synergies. The paper examines how DRR and adaptation can inform development to tackle the underlying drivers of disaster risk. Design/methodology/approach Based on a risk-based approach to the management of climate variability and change, the paper draws from a critical review of the literature on DRR and adaptation. The study finds that known and emerging risk from disasters continues to increase dramatically in many parts of the world, and that climate change is a key driver behind it. The authors also find that underlying causes of social vulnerability are still not adequately addressed in policy or practice. Linking DRR and adaptation is also complicated by different purposes and perspectives, fragmented knowledge, institutions and policy and poor stakeholder coordination. Findings The author’s analysis suggests that future work in DRR and adaptation should put a much greater emphasis on reducing vulnerability to environmental hazards, if there is truly a desire to tackle the underlying drivers of disaster and climate risks. Originality/value This will require coherent political action on DRR and adaptation aimed at addressing faulty development processes that are the main causes of growing vulnerability. The study concludes with a first look on the new Sendai Framework for Disaster Risk Reduction and how it aims to connect with adaptation and development.